Insights into Saudi Female International Students: Transition Experiences - Arafeh, Alia K (Journal of International Students, 2020)
This study explored the transition experiences of 10 Saudi female international students when they made the decision to study and live in the United States. The transition theory provided the theoretical foundation for understanding how Saudi female sophomore students progressed through moving to a Midwestern university. Ten in-depth individual interviews followed by a focus group interview with four of the participants elicited their reflections about their transition experiences evolving over time and the coping strategies they employed to facilitate their transition. The themes that emerged from data analysis emphasized the positive experiences of Saudi females in the United States, the importance of fathers’ support, desire to go back to Saudi Arabia upon graduation, and the several resources Saudi females sought other than campus support.